2021
DOI: 10.3390/agronomy11030418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Various Nitrogen Indices in N-Fertilizers with Inhibitors in Field Crops: A Review

Abstract: Nitrogen (N) management remains a global challenge for the sustainability of diversified farming systems. Field crops are often over-supplied with nitrogen by farmers aiming to high productivity. Although the increase of nitrogen rates leads in many instances to high yields, degree of effectiveness for nitrogen use remains low. Urease and nitrification inhibitors are technologies which have been present in the fertilizers market at least 50 years. Inhibitors exploitation ensures long-term nitrogen release and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 132 publications
0
24
1
Order By: Relevance
“…This could owe to more N availability in the root zone soil and minimum N losses to the surrounding environment. Folina et al [54] reported higher uptake by the field crops with coated N fertilizers. Likewise, deep placement of N fertilizer also enhanced N uptake by the rice crop [55].…”
Section: Discussionmentioning
confidence: 96%
“…This could owe to more N availability in the root zone soil and minimum N losses to the surrounding environment. Folina et al [54] reported higher uptake by the field crops with coated N fertilizers. Likewise, deep placement of N fertilizer also enhanced N uptake by the rice crop [55].…”
Section: Discussionmentioning
confidence: 96%
“…Above − ground N uptake = DM (kg ha −1 ) * Above−ground tissues N content (%) 100 ( 1) [25] Seed N uptake = Seed yield * seed N content (%) 100…”
Section: Equation Equation Number Referencementioning
confidence: 99%
“…In addition, Nitrogen Utilization Efficiency (NUtE) is another index that describes the amount of the ground-absorbed N that has been utilized by the plant for seed production [ 24 ]. These indices allow us to estimate the nitrogen losses, as well as the amount of nitrogen that has been absorbed by the crop [ 25 ] and, thus, the efficiency of the fertilization rate. However, these indices do not assess the overall performance of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, N uptake is definitely a second level trait influencing N efficiency [16]. Moreover, NHI and N content are fairly important nitrogen indexes for evaluation of slow-release fertilizers in crops, like durum wheat, for which N absorption (and therefore protein content) needs to be calculated [17].…”
Section: Introductionmentioning
confidence: 99%